Peoples and cultures of the world (Chantilly, Va. : The Teaching Company, 2004)
El profesor Fischer ofrece conferencias en antropología, sociedad, y costumbres; una comparación en común entre la sociedad precapitalista y la sociedad moderna.
pt.1. disc 1. The study of humanity ; the four fiels of anthropology ; culture and relativity ; fieldwork and the anthropological method ; nature, nurture, and human behavior ; languages, dialects, and social categories-- disc 2. Languaje and thought ; constructing emotions and identities ; magic, religion and codes of conduct ; rites of passage ; family, marriage, and incest ; multiple spouses and matrilineality-- part 2. disc 3. Gatherers and hunters ; headmen and horticulturists ; cannibalism and violence ; the role of reciprocity ; chiefdoms and redistribution ; cultural contact and colonialism-- disc 4. cultures of capitalism ; is economics rational? ; late capitalism-from ford to Disney ; the Maya resurgence in Guatemala and Mexico ; the Janus face of globalization
Lectures by Edward Fischer, Vanderbilt University.
Diálogo en inglés
Keywords: ANTROPOLOGIA; ETNOLOGÍA; CULTURA; VIDEOGRABACIONES